Book Review: Create, Copy, Disrupt: India’s Intellectual Property Dilemmas by Prashant Reddy T. & Sumathi Chandrashekan - Smith, Kevin L. (Journal of Copyright in Education & Librarianship, 2018)
Kevin L. Smith reviews Create, Copy, Disrupt: India’s Intellectual Property Dilemmas by Prashant Reddy T. & Sumathi Chandrashekan.